Multidrug-resistant Acinetobacter baumannii in healthcare settings in Africa - Agyepong, Nicholas; Fordjour, Francis; Owusu-Ofori, Alex (Frontiers in Tropical Diseases, 2023)
The emergence of multidrug-resistant Acinetobacter baumannii is a major concern to healthcare providers and facilities in many parts of the world. This bacterial pathogen is commonly implicated in hospital-acquired infections, particularly in critically ill patients admitted to the intensive care unit (ICU). The extensive use of antibiotics, particularly in ICUs, and the lack of proper infection control interventions in many hospitals have led to an increased emergence of multidrug-resistant A. baumannii. Infections due to multidrug-resistant A. baumannii are associated with prolonged hospital stays and high morbidity and mortality, particularly among hospitalized ICU patients. The lack of antibiotic stewardship programmes in many healthcare facilities has exacerbated the burden of A. baumannii infections in many parts of Africa. This review discusses the prevalence and antibiotic-resistance pattern of the multidrug-resistant A. baumannii, and the possible ways to address or minimise its emergence in healthcare settings in Africa.